Manajemen Sumber Daya Manusia di Sekolah Menengah Atas Tentang Konsep, Prinsip, Tantangan dan Solusi - Salmiati, Salmiati; Musyarapah, Musyarapah (PENG: Jurnal Ekonomi dan Manajemen, 2026)
Human Resource Management (HRM) in Senior High Schools (SMA) is a strategic approach to managing teaching and administrative staff. This article aims to examine the concepts, principles, challenges, and solutions for implementing HRM in secondary education. The concept of HRM emphasizes the integration of professional competence and noble morals, thus orienting not only toward performance but also toward character development. The underlying principles include justice ('adl), trustworthiness (amanah), professionalism (itqan), and deliberation in decision-making. In practice, the implementation of HRM faces various challenges, including a poor understanding of modern management values, limited competency among teaching staff, and the influence of globalization and digitalization, which tend to shift spiritual values. Furthermore, there are still obstacles in recruitment, development, and performance evaluation systems that do not fully integrate these principles. To address these challenges, strategic solutions are needed, including strengthening Islamic values-based training, developing a work culture in schools, and implementing a management system that adapts to technological developments without abandoning Sharia principles.